Influence of Brand Awareness, Brand Ambassador, on Purchase Decision Supported By Trust As The Intervening Variable on Shopee Marketplace - Bayu Kurniawan (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Nowadays, in the era of globalization, most Indonesian people are already aware of the changes in globalization. In further developments, the internet began to be used in all fields, including business. With the development of technology like this, more and more e-commerce and marketing companies and the number of internet users are increasing in Indonesia. This research is important due to inconsistencies in previous findings, which present both positive and negative results, so researchers try to take advantage of this gap to conduct further researchPurpose: The aim of this research is to determine the influence of Brand Awareness, Brand Ambassador, on Purchase Decision supported by Trust as the Intervening Variable on Shopee MarketplaceDesign/methodology/approach: This research determined 335 staff as the sample and implemented probability sampling processing simple random sampling methods applying Slovin Formula. The research is implementing AMOS 24 program as data analysis, and SEM AMOS approach in testing the hypothesisFindings/Result: The findings the brand awareness had a positive impact in partial towards purchase decisions. Brand ambassadors positively influence the trust, trust has an effect towards purchase decision, and brand awareness influence indirectly towards purchase decision which is mediated by trust in the Marketplace Shopee for staff of PT. XYZ IndonesiaConclusion: This study is to determine the effect of Brand Awareness, Brand Ambassador, on Purchase Decision with the support of Trust as an Intervening Variable on the Shopee Marketplace. The conclusion of the study is that Brand Awareness, Brand Ambassador have an effect on Purchase Decision with the support of Trust as an Intervening Variable on the Shopee MarketplaceOriginality/value (State of the art): This study makes a novel contribution by the integration of brand awareness, brand ambassadors and trust within the digital marketplace. While previous research literature revealed that brand awareness and brand ambassadors have an impact in the context of virtual marketplace but no attention was found on understanding the mediating role of trust in virtual purchasing decision Keywords: brand awareness, brand ambassador, purchase decision, trust, SEM-AMOS